Determining The Diet Quality, Sleep Quality and Obesity Status of Undergraduate Students: A Cross-Sectional Study - Özduran, Gülşen; Yücecan, Sevinç (Progress in Nutrition, 2022)
Summary. Objectives: Intake of an adequate and balanced diet and improved nutritional quality are factors that affect and increase sleep quality. Poor diet quality and sleep quality have been associated with chronic diseases such as obesity. This study aimed to evaluate relations among diet quality, sleep quality and obesity in undergraduate students. Materials and Methods: The study was conducted with 299 individuals studying at the Department of Nutrition and Dietetics of Near East University between September 2016 and January 2017. A questionnaire was administered to all participants and some anthropometric measurements were obtained to determine obesity status. Diet quality was assessed using the Diet Quality Index-International (DQI-I) tool and 3-day food record, and the Pittsburgh Sleep Quality Index (PSQI) was used to evaluate sleep quality. Results: The body mass index (BMI) values showed that 13.7% of the students were underweight, 68.9% were of normal, 12.7% were overweight and 4.7% were obese. Diet quality was poor in 89.3% and sleep quality was poor in 44.1% of the students. 4.9% of the students with good diet quality and 4.5% of the students with poor diet quality were obese, and 4.8% of the students with good sleep quality and 4.5% of the students with poor sleep quality were obese. Total DQI-I scores were negatively correlated and significantly associated with total PSQI scores (p<0.05) but BMI was not significantly associated with total DQI-I and PSQI scores (p>0.05). Conclusion: It was observed that improved diet quality was associated with better sleep quality. The study findings supported the primary hypothesis that improved diet quality will result in better sleep quality. More comprehensive studies in larger samples are warranted to conclusively determine relations among diet quality, sleep quality and obesity status.